Kualitas Semen Beku Kuda dalam Pengencer Susu Skim dan Dimitropoulos dengan Dimetilformamida Sebagai Krioprotektan - I Arifiantini; I Supriatna; . Aminah (Media Peternakan, 2007)
Equine semen are far less tolerant in the freezing and thawing process than bull semen. The stallion spermatozoa are known susceptible to cold-shock relating with the content of their fatty acid on the plasma membrane. The extender is one of determining factors in the success of stallion semen cryopreservation, as an energy source and protector the cell from harmfull effect of cold shock. The common cryoprotective agent (CPA) for mammalian spermatozoa was glycerol, but for stallion semen cryopreservation, dimethyl formamide (DMF) was more suitable. This research was conducted to compare the success of the stallion semen cryopreservation in skim milk and dimitropoulos (DV) extender with DMF as cryoprotectant. Semen from three sexualy mature stallions was collected twice a week using an artificial vagina. Semen was evaluated macro- and microscopically and then divided into two tubes, diluted each of them with skim milk dan DV extender (1:1), centrifuged at 3 000 rpm for 15 minutes. The supernatant was removed and the pellet (spermatozoa) was re-diluted in skim DMF (SDMF) and DVDMF extender with the concentration of spermatozoa was 200x106 ml-1. The semen then packed in 0.3ml minitub straw equilibrated for two hours at 4-50C and frezee in liquid N2 vapor for 10 minutes. The assessment of sperm quality was conducted based on the percentage of sperm motility and viability. In this research, post-thawed semen in DVDMF showed the percentages of the motility (36.2%) and the viability (59.3%) higher (P < 0.05) than SDMF (28.5 and 48.0 %). In conclusion, the DVDMF extender provided better post-thawed semen quality than SDMF. Key words: cryopreservation, stallion semen, skim, dimitropoulos, dimethyl formamide